Estimation of Raindrop Size Distribution Parameters Using Lightning Data over West Sumatra - Salma, Faridah; Marzuki, Marzuki; Hashiguchi, Hiroyuki; Nauval, Fadli (Jurnal Ilmu Fisika, 2021)
In situ observations of raindrop size distributions (DSDs) are still limited, especially in the tropics. Therefore, this study develops an alternative method to calculate DSD parameters by utilizing lightning data from the World-Wide Lightning Location Network (WWLLN) observation. DSD data was obtained from Parsivel's observations in the equatorial regions of Indonesia, i.e., Kototabang (100.32◦E, 0.20◦S, 865 m above mean sea level/ASL), Padang (100.46°E, 0.915°S, 200 m ASL), and Sicincin (100.30°E, 0.546°S, 134 m ASL). A gamma distribution parameterized the DSD. Three analysis domains were examined, with a grid of 0.1° x 0.1°, 0.5° x 0.5°, and 1° x 1°.  We examined the possibility to calculate the near-instantaneous DSD parameter, so three short time intervals, namely, one, five and ten minutes, were used. The results showed that the number of lightning strokes does not adequately correlate with DSD parameters. This is observed in all time intervals and analysis domains. Thus, the use of lightning data to calculate DSD parameters is not possible for short time interval of DSD (near instantaneous DSD). However, lightning data can estimate the average DSD parameters for an average time of more than one hour, as recommended by previous studies.